2013
DOI: 10.1038/nbt.2566
|View full text |Cite
|
Sign up to set email alerts
|

Identification of direct targets and modified bases of RNA cytosine methyltransferases

Abstract: The extent and biological impact of RNA cytosine methylation are poorly understood, in part owing to limitations of current techniques for determining the targets of RNA methyltransferases. Here we describe 5-azacytidine-mediated RNA immunoprecipitation (Aza-IP), a mechanism-based technique that exploits the covalent bond formed between an RNA methyltransferase and the cytidine analog 5-azacytidine to recover RNA targets by immunoprecipitation. Targets are subsequently identified by high-throughput sequencing.… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

9
377
1
1

Year Published

2015
2015
2023
2023

Publication Types

Select...
7
2
1

Relationship

0
10

Authors

Journals

citations
Cited by 393 publications
(388 citation statements)
references
References 40 publications
(67 reference statements)
9
377
1
1
Order By: Relevance
“…A few studies have also utilized RNA bisulfite sequencing to map RNA m5C marks at the transcriptome level and found evidence for the presence of m5C in mammalian mRNAs and noncoding RNAs (Squires et al 2012;Hussain et al 2013b;Khoddami and Cairns 2013;Amort et al 2017). While it has been suggested that the human coding and noncoding transcriptome contains up to 10,000 methylation sites (Squires et al 2012;Amort et al 2017), the function of these marks has remained elusive.…”
Section: [Supplemental Materials Is Available For This Article]mentioning
confidence: 99%
“…A few studies have also utilized RNA bisulfite sequencing to map RNA m5C marks at the transcriptome level and found evidence for the presence of m5C in mammalian mRNAs and noncoding RNAs (Squires et al 2012;Hussain et al 2013b;Khoddami and Cairns 2013;Amort et al 2017). While it has been suggested that the human coding and noncoding transcriptome contains up to 10,000 methylation sites (Squires et al 2012;Amort et al 2017), the function of these marks has remained elusive.…”
Section: [Supplemental Materials Is Available For This Article]mentioning
confidence: 99%
“…Recent studies have provided detailed maps of the location and abundance of a handful of RNA modifications (Dominissini et al 2012;Meyer et al 2012;Khoddami and Cairns 2013;Carlile et al 2014;Schwartz et al 2014a;Delatte et al 2016), mostly obtained by coupling antibody immunoprecipitation or chemical treatments to next-generation sequencing. Through these approaches, N 6 -methyladenosine (m 6 A) modification has been identified as an important factor in the determination of mammalian cell fate transition and embryonic stem cell differentiation (Batista et al 2014;.…”
Section: Introductionmentioning
confidence: 99%
“…3 Mapping of m 5 C in RNA was initially attempted by adapting the bisulfite sequencing technology used for m 5 C in DNA, leading to the identification of approximately 10,000 m 5 C sites in mRNA. 26,27 Subsequently, new methods were developed that leverage m 5 C methyltransferases to enrich m 5 C-containing RNA, either by incorporating 5-azacytidine into RNA, 28 or by mutating the methyltransferase 29 to enable modified RNA capture. These methods identified far fewer m 5 C sites in mRNA, on the order of a few hundred to one thousand, respectively.…”
Section: Mrnamentioning
confidence: 99%